Measure for measure: Comparing morphological and biomass traits for sex allocation in two gynodioecious species1. Issue 6 (1st June 2013) - Sakai, Ann K.; Weller, Stephen G.; Campbell, Diane R.; Culley, Theresa M.; Dunbar‐Wallis, Amy K.; Andres, Allen M.
Abstract : Premise of the study: Sex allocation models assume male and female traits are measured in a common currency, allocation traits show heritability, and tradeoffs between investment in the two sexual functions occur. The potential for model predictions and genetic parameters to depend on the currency used is not well understood, despite frequent use of measures not in a common currency. Methods: We analyzed the relationship between common currency (biomass of carpels, seeds, and stamens) measures and morphological measures (numbers of ovules, seeds, and pollen) in Schiedea salicaria (12–13% females) and S. adamantis (39% females), two closely related gynodioecious species. Additionally, we compared heritabilities and genetic correlations for male and female allocation between these two types of measures. Key results: Ovule, seed, and pollen number show greater sexual dimorphism in S. adamantis than in S. salicaria . Most but not all morphological traits and analogous biomass traits are highly correlated with a linear relationship. Narrow‐sense heritabilities based on the two methods are often similar, but higher for ovule number than carpel mass and lower for anther number than stamen mass in S. adamantis . Neither trait type shows negative genetic correlations between male and female function. onclusions: Both trait types show greater sexual dimorphism in S. adamantis, and significant heritabilities suggest that morphological traits will continue to evolve with breeding system changes. Although most relationships between morphological and biomass traits are linear, curvilinear relationships for two traits suggest that caution is warranted if morphological and common currency traits are used interchangeably in fitness gain curves.